Mutations of the CYP21A2 gene: Association of p.V281L mutation with polycystic ovarian syndrome (PCOS): Mutacije v CYP21A2 genu: povezava p.V281L mutacije s sindromom policističnih jajčnikov (PCOS) - Stangler Herodež, Špela; Fijavž, Lusien; Zagradišnik, Boris; Došen, Marko; Takač, Iztok; Kokalj-Vokač, Nadja (Acta Medico-Biotechnica, 2021)
Purpose: The CYP21A2 gene encodes the enzyme 21–hydroxilase, which is responsible for the production of steroids. These hormones are key mediators of sexual development and conception. Patients with 21–hydroxilase deficiency tend to be affected in different stages of life. The purpose of this study was to compare the genetic profiles of women with unexplained infertility problems with the genetic profiles of healthy controls. Furthermore, were analyzed associations between mutations of the CYP21A2 gene and various clinical and laboratory parameters.Methods: We enrolled 300 women, diagnosed with unexplained infertility problems, into this retrospective study. For each subject, we recorded important clinical and laboratory parameters during different phases of the menstrual cycle. In the control group, we enrolled 100 samples. Each subject provided a blood sample, which was used to isolate DNA for subsequent polymerase chain reaction (PCR).Results: In total, 11.6% of the test subjects exhibited significant hormonal deviations (HD) (estrogens and/ or progestins and/or total testosterone) and 5.3% were diagnosed with polycystic ovarian syndrome (PCOS). We identified a significant association between the p.V281L mutation and the frequency of test subjects with significant HD (x2=6.99, p=0.01). A similar association was also observed between p.V281L mutation and the frequency of test subjects with PCOS (x2=16.78, p=0.00). However, we did not establish any associations between the frequency of mutations in test subjects when compared with controls. In addition, we did not find any significance in the frequency of CYP21A2 gene mutations and any of the laboratory parameters tested.Conclusion: Our results identify a significant association of the p.V281L mutation in the CYP21A2 gene with the frequencies of both PCOS and significant HD.
Keywords: p.V281L mutation; CYP21A2 gene; polycystic ovarian syndrome; PCOS